Mnemonic Similarity Task: A Tool for Assessing Hippocampal Integrity. Issue 11 (November 2019) - Stark, Shauna M.; Kirwan, C. Brock; Stark, Craig E.L.
Abstract : The hippocampus is critical for learning and memory, relying in part on pattern separation processes supported by the dentate gyrus (DG) to prevent interference from overlapping memory representations. In 2007, we designed the Mnemonic Similarity Task (MST), a modified object recognition memory task, to be highly sensitive to hippocampal function by placing strong demands on pattern separation. The MST is now a widely used behavioral task, repeatedly shown to be sensitive to age-related memory decline, hippocampal connectivity, and hippocampal function, with specificity to the DG. Here, we review the utility of the MST, its relationship to hippocampal function, its utility in detecting hippocampal-based memory alterations across the lifespan, and impairments associated with clinical pathology from a variety of disorders. Highlights: The Mnemonic Similarity Task (MST), a modified object recognition memory task, is highly sensitive to hippocampal function, placing strong demands on pattern separation processes. A variety of MST versions have been developed to address specific issues, but they all share the feature that as lure similarity increases, accurate discrimination decreases. The MST has been used to identify hippocampal dysfunction associated with healthy aging, dementia, schizophrenia, depression, and other clinical disorders. The sensitivity and reliability of the MST make it an extremely valuable tool for tracking progression of disease or decline and critical for determining the effectiveness of treatments, both pharmaceutical and behavioral.